Jijel province dataset for wildfire susceptibility assessment - Matougui, Zakaria (PANGAEA, 2024)
This dataset comprises multiple geospatial layers used to analyse various environmental factors and their temporal variations. It includes burned areas, elevation, land surface temperature (LST), rainfall, wind speed, and vegetation indices, among other parameters. The data span different periods and spatial resolutions, offering insights into both recent and historical conditions. Burned areas data, with a resolution of 500 m, were sourced from MODIS and cover the years 2001 to 2023. Elevation data, at a 30 m resolution, was derived from ALOS PALSAR and pertains to the period between 2006 and 2011. The LST data, with a 1000 m resolution, also from MODIS, represents mean values from 2000 to 2023. Rainfall measurements, with a 5566 m resolution, are provided by the Climate Hazards Group InfraRed Precipitation with Station Data (CHIPS) and cover the mean period from 2000 to 2023. Wind speed data, with a resolution of 4638.3 m, was obtained from TerraClimate and spans the same mean period as the rainfall data. NDVI measurements, at a 250 m resolution, are from MODIS and cover the years 2000 to 2023. Roads data are from OpenStreetMap, reflecting the year 2019. Landform data, at a 90 m resolution, is derived from Global ALOS Landform (Theobald et al., 2015) for the period 2006 to 2011. Finally, population density data, with a 1000 m resolution, is provided by WorldPop and covers the mean period from 2000 to 2020. This dataset is designed to support studies on environmental changes, land use, and population impacts, providing a comprehensive resource for researchers and policymakers. The data were collected using various remote sensing technologies and sources, ensuring a broad temporal and spatial coverage to enhance the understanding of environmental dynamics.
Keywords: burned area; climate; elevation; Jijel; landform; Land surface temperature; NDVI; population density; rainfall; topography; wildfire; wind speed